Volume Controller using Hand Gestures - Tiwari, Saransh; Mishra, Abhineet; Kukreja, Deepak; Yadav, Anup Lal (International Conference on Computing, Communication, and Networking Technologies (Online), 2023)
This work presents the development of a volume controller using hand gestures as the input to control the system.This system uses the OpenCV module to detect and control gestures. The application captures images and videos from the webcam, and based on the user's input, it controls the volume of the system.Hand gesture recognition systems have a wide range of applications, including volume control, navigation, gaming, and sign language interpretation.In this project, we are developing a hand gesture volume controller system. The system uses a high-resolution camera to detect hand gestures, which are then used to control the volume of a device. The system is developed using the Numpy, OpenCV, and Python packages.The system is designed to be intuitive and easy to use. Users can simply make a gesture with their hand to control the volume of the device. The hand gesture volume controller system has the potential to revolutionize the way we interact with devices. By allowing us to control devices with our hands, hand gesture recognition systems can make our lives easier and more convenient.